2001
DOI: 10.1149/1.1362541
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Characterization of High Power Lithium-Ion Batteries for Use in Hybrid Electric Vehicles

Abstract: A baseline cell chemistry was identified as a carbon anode, LiNi 0.8 Co 0.2 O 2 cathode, and diethyl carbonate-ethylene carbonate LiPF 6 electrolyte, and designed for high power applications. Nine 18650-size advanced technology development cells were tested under a variety of conditions. Selected diagnostic techniques such as synchrotron infrared microscopy, Raman spectroscopy, scanning electronic microscopy, atomic force microscopy, gas chromatography, etc., were used to characterize the anode, cathode, curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
157
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(164 citation statements)
references
References 9 publications
4
157
3
Order By: Relevance
“…While the cycled anode showed a capacity loss of 10% when compared to a fresh anode, the potential profiles for charging and discharging are almost same to for the two anodes pieces. Previous studies of anode pieces recovered from cycled 18650's showed large film impedance that was removed by continuous cycling and reduction in fresh electrolyte [6]. This behavior was not observed here, probably because any degradation films left on the anode was removed altogether by washing before assembling into the cell with lithium.…”
Section: Electrochemical Analysis Of Cell Componentscontrasting
confidence: 41%
See 3 more Smart Citations
“…While the cycled anode showed a capacity loss of 10% when compared to a fresh anode, the potential profiles for charging and discharging are almost same to for the two anodes pieces. Previous studies of anode pieces recovered from cycled 18650's showed large film impedance that was removed by continuous cycling and reduction in fresh electrolyte [6]. This behavior was not observed here, probably because any degradation films left on the anode was removed altogether by washing before assembling into the cell with lithium.…”
Section: Electrochemical Analysis Of Cell Componentscontrasting
confidence: 41%
“…Zhang and co-workers reported that LiPF 6 salt is not stable at elevated temperature and is decomposed to PF 5 (g) and LiF (s). [6] They also observed that electrolyte turned a brown color by the reaction of PF 5 gas and LP40 electrolyte. We also observed a brown stain on the separator after disassembly of cycled cell.…”
Section: Cycling Capacity At Elevated Temperaturementioning
confidence: 96%
See 2 more Smart Citations
“…The interest in lithium rechargeable batteries in electric vehicles (EVs) has been significantly increased in recent years [1][2][3]. The important factors for their application are low price, long cycle life, environmental safety, and high specific energy.…”
Section: Introductionmentioning
confidence: 99%